Penimbunan dan Manipulasi Supply Dalam Perspektif Ekonomi Islam - s, Wibi Nugraha Faturrizky; Jenuri (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2024)
This study aims to examine the practice of hoarding and supply manipulation in the context of Islamic economics. The research employs a literature review method to investigate Islamic perspectives on these practices and their impacts on society. The findings indicate that hoarding and supply manipulation contradict the principles of Islamic economics, leading to market instability and exacerbating economic disparities. It also discusses the strategies and policies needed to address this phenomenon, including the roles of governments, Islamic financial institutions, and community groups. In conclusion, effective handling of hoarding and supply manipulation is crucial to maintain justice and balance in economic activities, aligning with Islamic principles. Keywords: Hoarding, Supply Manipulation, Islamic Economics